Physiological and biomechanical responses to an acute bout of high kicking in dancers - Rice, P. E.; Gurchiek, R. D.; McBride, J. M. (The Journal of Strength and Conditioning Research, 2018)
High-kick precision competitive dance involves the integration of kicking inline, jumping, and turning during a 3-minute routine and causes a disturbance to both aerobic and anaerobic systems. However, no known study has quantified the effect of a hick-kick-specific protocol on blood lactate (BL), heart rate (HR), and countermovement jump (CMJ) performance. A group of adolescent high-kick dancers (n = 20; age = 15.0 ± 1.8 years; height = 161.5 ± 8.2 cm; body mass = 56.3 ± 11.0 kg; and dance team/weight lifting experience = 2.1 ± 0.9 years) participated in this investigation. Participants' BL was collected, and 3 CMJ trials were performed before (PRE) and after (POST) completing the high-kick protocol. The high-kick protocol consisted of intermittent running and kicking in place for a total of 1:45 at a tempo of 160 b/min, while average and peak HR (HRavg; HRpeak) were recorded. Jump height (JH), maximal trunk flexion (MTF), take-off angle (TOA), and relative peak power (PP) were determined from PRE and POST CMJ trials. During kicking, HRavg and HRpeak (n = 13) were 172.4 ± 15.7 b/min and 207.0 ± 23.0 b/min, respectively. Dancers' (n = 20) BL significantly (p = 0.05) increased from 1.5 ± 0.5 to 8.6 ± 1.5 mmol/L, and JH and PP significantly decreased from 0.42 ± 0.08 to 0.36 ± 0.04 m and 41.3 ± 5.5 to 38.5 ± 4.0 W/kg, respectively, from PRE to POST. No significant changes occurred in MTF and TOA measurements from PRE to POST. The demands introduced during a high-kick-specific protocol can therefore be recognized as a metabolic and mechanical stimulus for fatigue; however, esthetics seem to be unaffected. Such findings may indicate that this modality of dance necessitates supplemental strength and conditioning training similar to other sports to sustain the loads of high-kick dance.